The Hands-Off Investor: An Insider’s Guide to Investing in Passive Real Estate Syndications - Chaudhary, Amita (Gyan Management Journal, 2021)
This book has five sections. Section 1 pertains to the lay of the land which forms the basis of knowledge for the topics that are covered in the book.